Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Species of fast bulk‐soil nutrient cycling have lower rhizosphere effects: A nutrient spectrum of rhizosphere effects - Lijuan Sun; Yuki Tsujii; Tianle Xu; Mengguang Han; Rui Li; Yunfeng Han; Dayong Gan; Biao Zhu (Ecology, 2023)
Tree roots not only acquire readily‐usable soil nutrients but also affect microbial decomposition and manipulate nutrient availability in their surrounding soils, that is, rhizosphere effects (REs). Thus, REs challenge the basic understanding of how plants adapt to the environment and co‐exist with other species. Yet, how REs vary among species in response to species‐specific bulk soil nutrient cycling is not well‐known. Here, we studied how plant‐controlled microbial decomposition activities in rhizosphere soils respond to those in their corresponding bulk soils and whether these relations depend on species‐specific nutrient cycling in the bulk soils. We targeted 55 woody species of different clades and mycorrhizal types in three contrasting biomes, namely a temperate forest, a subtropical forest, and a tropical forest. We found that microbial decomposition activities in rhizosphere soils responded linearly to those in their corresponding bulk soils at the species level. Thereafter, we found that REs (parameters in rhizosphere soils minus those in corresponding bulk soils) of microbial decomposition activities had negative linear correlations with microbial decomposition activities in corresponding bulk soils. A multiple factor analysis revealed that soil organic carbon, total nitrogen, and soil water content favored bulk soil decomposition activities in all three biomes, showing that the magnitude of REs varied along a fast‐slow nutrient cycling spectrum in bulk soils. The species of fast nutrient cycling in their bulk soils tended to have smaller or even negative REs. Therefore, woody plants commonly utilize both positive and negative REs as a nutrient‐acquisition strategy. Based on the trade‐offs between REs and other nutrient‐acquisition strategies, we proposed a push and pull conceptual model which can bring plant nutrient‐acquisition cost and plant carbon economics spectrum together in the future. This model will facilitate not only the carbon and nutrient cycling but also the mechanisms of species co‐existence in forest ecosystems.

Effects of warming and grazing on soil N availability, species composition, and ANPP in an alpine meadow - Shiping Wang; Jichuang Duan; Guangping Xu; Yanfen Wang; Zhenhua Zhang; Yichao Rui; Caiyun Luo; Burenbayin Xu; Xiaoxue Zhu; Xiaofeng Chang; Xiaoyong Cui; Haishan Niu; et al. (Ecology, 2012)
Uncertainty about the effects of warming and grazing on soil nitrogen (N) availability, species composition, and aboveground net primary production (ANPP) limits our ability to predict how global carbon sequestration will vary under future warming with grazing in alpine regions. Through a controlled asymmetrical warming (1.2/1.7°C during daytime/nighttime) with a grazing experiment from 2006 to 2010 in an alpine meadow, we found that warming alone and moderate grazing did not significantly affect soil net N mineralization. Although plant species richness significantly decreased by 10% due to warming after 2008, we caution that this may be due to the transient occurrence or disappearance of some rare plant species in all treatments. Warming significantly increased graminoid cover, except in 2009, and legume cover after 2008, but reduced non‐legume forb cover in the community. Grazing significantly decreased cover of graminoids and legumes before 2009 but increased forb cover in 2010. Warming significantly increased ANPP regardless of grazing, whereas grazing reduced the response of ANPP to warming. N addition did not affect ANPP in both warming and grazing treatments. Our findings suggest that soil N availability does not determine ANPP under simulated warming and that heavy grazing rather than warming causes degradation of the alpine meadows.